2020
DOI: 10.1111/oik.07311
|View full text |Cite
|
Sign up to set email alerts
|

Nest attentiveness drives nest predation in arctic sandpipers

Abstract: Most birds incubate their eggs to allow embryo development. This behaviour limits the ability of adults to perform other activities. Hence, incubating adults trade off incubation and nest protection with foraging to meet their own needs. Parents can either cooperate to sustain this tradeoff or incubate alone. The main cause of reproductive failure at this reproductive stage is predation and adults reduce this risk by keeping the nest location secret. Arctic sandpipers are interesting biological models to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 103 publications
3
26
1
Order By: Relevance
“…Because Arctic-breeding shorebirds are primarily income breeders (Klaassen et al, 2001;Piersma et al, 2003, but see Hobson and Jehl, 2010), changes in the timing and abundance of invertebrates may in turn affect shorebird nest attendance due to adult food limitations (Tulp and Schekkerman, 2006;Reneerkens et al, 2011). Adults leaving nests unattended or making more trips away from the nest may increase the likelihood of predation by reducing crypsis of the eggs (adults are better camouflaged than eggs themselves) or drawing attention to the nest (activity near a nest can reveal its location, Smith et al, 2007Smith et al, , 2012Reneerkens et al, 2011;Bulla et al, 2016;Meyer et al, 2020). But evidence linking warm springs with increased nesting success is equivocal; Weiser et al (2018a) found limited evidence for such a relationship, with only two of 14 species investigated across a broad geographic region of the Arctic having higher nest survival in warm springs.…”
Section: Introductionmentioning
confidence: 99%
“…Because Arctic-breeding shorebirds are primarily income breeders (Klaassen et al, 2001;Piersma et al, 2003, but see Hobson and Jehl, 2010), changes in the timing and abundance of invertebrates may in turn affect shorebird nest attendance due to adult food limitations (Tulp and Schekkerman, 2006;Reneerkens et al, 2011). Adults leaving nests unattended or making more trips away from the nest may increase the likelihood of predation by reducing crypsis of the eggs (adults are better camouflaged than eggs themselves) or drawing attention to the nest (activity near a nest can reveal its location, Smith et al, 2007Smith et al, , 2012Reneerkens et al, 2011;Bulla et al, 2016;Meyer et al, 2020). But evidence linking warm springs with increased nesting success is equivocal; Weiser et al (2018a) found limited evidence for such a relationship, with only two of 14 species investigated across a broad geographic region of the Arctic having higher nest survival in warm springs.…”
Section: Introductionmentioning
confidence: 99%
“…This circumpolar network of study sites (the "Interactions Working Group")offersalargediversity of productivity and temperature conditions within the Arctic biome ( Fig. S1; Meyer et al, 2020).…”
Section: Study Sitesmentioning
confidence: 99%
“…Nests were found systematically by rope-dragging or opportunistically by walking through suitable breeding habitat, flushing incubating birds and/or following them visually as they walk back to their nest. Between one and three Calidris species were monitored at each site (Table S1; see distribution of species and location of study sites on figure 1 in Meyer et al, 2020).…”
Section: Study Animals and Nest Detectionmentioning
confidence: 99%
See 2 more Smart Citations